The color of the third degree racism, police torture, and civil rights in the American South, 1930-1955 - Niedermeier, Silvan 1981- (University of North Carolina Press, 2019)
Police torture and "legal lynchings" in the American South -- Torture and African American courtroom testimony -- The NAACP campaign against "forced confessions" -- Selective public outrage: the Quintar South case -- The investigations by the federal government
Translation of: Rassismus und Bürgerrechte : Polizeifolter im Süden der USA, 1930-1955. Hamburg : Hamburger Edition, 2014
Includes bibliographical references and index
Keywords: Geschichte 1930-1955; African Americans / Civil rights / Southern States / History / 20th century; Police brutality / Southern States / History / 20th century; Torture / Southern States / History / 20th century; African American prisoners / Violence against / Southern States / History / 20th century; Racism / Southern States / History / 20th century; Beschuldigter; Folter; Schwarze; Justizvollzugsbeamter; Polizeibeamter; Rassismus; Strafgefangener; Southern States / Race relations / History / 20th century; USA -- Südstaaten; Hochschulschrift